Evaluation of low-cost technology options for sustainable water supply and sanitation in two peri-urban areas of Lusaka, Zambia: opportunities and constraints - Chiliboyi, Yvonne (Rhodes University, Faculty of Science, Institute for Water Research, 2017)
Presently, at least 70% of the total urban population in Zambia resides in peri-urban areas. Peri-urban settlements are characterized by high population growth, high poverty levels and inadequate access to water and sanitation which often result in increased prevalence of diseases. The situation is even made worse because of the position that many local authorities have taken regarding the implementation of infrastructure and service development in these settlements. Local authorities in developing countries have continuously focused on implementation of traditional and unsustainable technologies for service provision to meet the demand despite the technologies' inability to serve the rapidly growing peri-urban areas. These technologies have high costs, lack proper operation and maintenance, and are not affordable to majority of peri-urban residents. Therefore, this study was set out to identify and evaluate the existing and possible low-cost technology options for sustainable water supply and sanitation in two selected peri-urban areas of Lusaka, Zambia, namely Kanyama and Chazanga. This was achieved through a household survey conducted in the selected communities. Questionnaires and focus group discussions were held in the respective areas to obtain baseline data on the current water supply and sanitation situation, the type of technologies used, challenges faced regarding water and sanitation technologies, and to get the communities perceptions and preferences of different technology options. Thereafter, a Multi-Criterion Analysis methodological approach was used to assess the selected technologies by the communities, taking into consideration of the economic, socio-cultural, technical, institutional and environmental aspects. Results from the study revealed that a few low-cost water supply and sanitation technologies are feasible for peri-urban areas. For Chazanga, communal taps, boreholes, protected wells, and rain water harvesting were found to be feasible for water supply. For sanitation, on-site sanitation services such as compost toilets, dry toilets, as well as Ventilated Improved Pits (VIP) and Pour-flush, Fossa Alterna and the Urine Diversion Dry Toilet (UDDT) are some of the low-cost technologies that can be implemented in the area. The VIP is suitable for households that rely on water from communal taps for their use. As majority of households in the area have taps on their plots, the Pour-flush can be an alternative. The Fossa Alterna and the Urine Diversion Dry Toilet (UDDT) have low initial cost and can accommodate different households. Additionally, the area has a lower household size and majority of the residents in the area landlords, which makes it easy to teach users how the toilet operates as well as its maintenance. For Kanyama, feasible and sustainable low-cost water supply facilities include boreholes and communal taps. Kanyama has limited plot sizes thereby causing the challenge of implementing infrastructure such as rainwater harvesting. Additionally, continuous increase in urban population in the area, coupled with the construction of unregulated households and sanitation facilities, renders protected wells not feasible to implement in Kanyama. In terms of sanitation, wet on-site sanitation facilities such as Ventilated Improved Pit (VIP) latrines are accepted by the community. The VIP does not require water for use and if properly constructed can be used as a bathroom. The Pour-flush toilet is also another alternative for provision of sanitation in the area. However, the latrine can be expensive to construct for majority of the residents. Dry sanitation such as the Urine Diversion Dry Toilet (UDDT) is not feasible for Kanyama. The UDDT requires continuous awareness on its use especially in rented households where tenants are constantly changing. The method of evaluating appropriate technology options for peri-urban areas and thereafter letting the users from the communities choose from the proposed technologies ensures a participatory approach. Results from Multi-Criterion Analysis (MCA) showed that stakeholders' influence is essential for the selection of sustainable technology options. However, it is important that the implementation process of any technology in peri-urban areas consider different aspects including the local environmental, socio-cultural, economic, technical, and institutional conditions. Finally, the outcome of this study will not only provide baseline data for successful implementation of appropriate low-cost water supply and sanitation technology options in Chazanga and Kanyama, but also other peri-urban communities in Zambia.
Keywords: Toilets -- Technological innovations -- South Africa; Sanitary engineering -- Technological innovations -- South Africa; Water resoures development -- Technological innovations -- South Africa; Water-supply -- Technological innovations -- South Africa; Household surveys -- South Africa